Analisis Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Sayur Di Pasar Segiri Kota Samarinda - Ednaldy Syahrimmunandar Samad; Jiuhardi Jiuhardi; Diana Lestari (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2018)
Analysis of Factors Affecting the Income of Vegetable Traders in the Segiri Market in Samarinda City, Under the Guidance of Jiuhardi as mentor I, and Diana Lestari as mentor II.The purpose of this research is to analyze the factors of income of traders in the Segiri market in Samarinda. The types and sources of data used in this study are primary data and trader data at the regional technical implementation unit office market of segiri in 2019. Data collection techniques used are field research and the analytical tool used is a multiple linear regression analysis tool. Existing data is processed using the SPSS (Statistical package for social science) computer program version 20.The results of the analysis show that business capital, business location, business length, and working hours together significantly influence the income of Segiri Market traders in Samarinda City.